2019
DOI: 10.1021/acs.macromol.9b00171
|View full text |Cite
|
Sign up to set email alerts
|

Isophthalate-Based Room Temperature Phosphorescence: From Small Molecule to Side-Chain Jacketed Liquid Crystalline Polymer

Abstract: Isophthalate with the simple chemical structure is identified as an effective phosphor for room temperature phosphorescent (RTP) materials. With −Br, −CH 3 , and −CHCH 2 at the 5-position of the benzene ring of didecyl isophthalate, the three crystalline small molecules of DDIP-Br, DDIP-CH 3 , and DDIP-CHCH 2 demonstrate ultralong RTP with lifetime of 236, 650, and 184 ms, respectively, although no specific interactions are recognized in the crystals. Radical polymerization of DDIP-CHCH 2 readily results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…Multichain column models have been suggested for some other side-chain polymers of which the side chains are dendron-like, , hemiphasmid-like, fork-like, , or linear. It is generally acknowledged that the backbone bundle lies in the column center as illustrated in Scheme a. Considering the special supramolecular organization of phasmidic molecules, the model shown in Scheme b may be more reasonable for PNB-12.…”
Section: Resultsmentioning
confidence: 99%
“…Multichain column models have been suggested for some other side-chain polymers of which the side chains are dendron-like, , hemiphasmid-like, fork-like, , or linear. It is generally acknowledged that the backbone bundle lies in the column center as illustrated in Scheme a. Considering the special supramolecular organization of phasmidic molecules, the model shown in Scheme b may be more reasonable for PNB-12.…”
Section: Resultsmentioning
confidence: 99%
“…In 2019, Chen and co‐workers first achieved RTP emission from a liquid crystalline polymer system without strong intermolecular interactions or covalent cross‐links through designing and synthesizing a series of isophthalate derivatives based RTP materials with only weak intermolecular interactions, including small molecules, compounds 14–16, and polymer P6 (Schemes 1c and 2). [ 66 ] Single‐crystal analyses of those small molecules revealed that only weak Van der Waals interactions existed between the molecules ( Figure a–c). The resultant system offered a new strategy to construct applicable RTP materials in the liquid crystalline state, in which the polymer structure and the side‐chain jacketing effect provided enough restriction for suppressing the phosphors’ movement to a great extent, thus emitting green phosphorescence after cyan fluorescence (Figure 8d).…”
Section: Nondoped Polymer Systems With Rtp Emissionmentioning
confidence: 99%
“…[22][23][24] Apart from noncovalently doping systems, covalently embedding organic phosphors into polymer matrices is also an efficient strategy to achieve organic amorphous RTP materials. [25][26][27][28][29][30] For instance, Fraser and co-workers firstly reported a single-component polymer exhibiting fluorescence/phosphorescence dual emissions by covalently linking boron difluoride dibenzoylmethane into the terminal of poly(lactic acid) (PLA). 1a Also, Ma et al proposed a universal strategy to achieve efficient RTP through radical binary copolymerization of acrylamide and various organic phosphors.…”
Section: Introductionmentioning
confidence: 99%